The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1021/acs.orglett.2c00018
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Polycyclic Isoindolines via α-C–H/N–H Annulation of Alicyclic Amines

Abstract: Relatively unstable cyclic imines, generated in situ from their corresponding alicyclic amines via oxidation of their lithium amides with simple ketone oxidants, engage aryllithium compounds containing a leaving group on an ortho-methylene functionality to provide polycyclic isoindolines in a single operation. The scope of this transformation includes pyrrolidine, piperidine, azepane, azocane, and piperazines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 82 publications
1
2
0
Order By: Relevance
“…We were pleased to find that imines 2 generated by our method can be intercepted with trimethylsilyl cyanide (TMSCN) to provide α-aminonitriles 3 in moderate to good yields . In line with our prior work, the use of trifluoroacetophenone as the ketone oxidant typically resulted in the highest yields . The scope of this transformation is quite broad (Scheme ).…”
supporting
confidence: 81%
See 1 more Smart Citation
“…We were pleased to find that imines 2 generated by our method can be intercepted with trimethylsilyl cyanide (TMSCN) to provide α-aminonitriles 3 in moderate to good yields . In line with our prior work, the use of trifluoroacetophenone as the ketone oxidant typically resulted in the highest yields . The scope of this transformation is quite broad (Scheme ).…”
supporting
confidence: 81%
“…Based on the known ability of lithium amides (e.g., 1 ) to undergo imine formation (e.g., 2 ) upon reducing simple ketones, , a process that we have found to be rapid for lithium amides derived from alicyclic amines, we recently developed a new strategy for amine α-C–H bond functionalization (Scheme d) . Various α-functionalized amines can be accessed with this approach.…”
mentioning
confidence: 99%
“…For instance, we have shown that polycyclic lactams can be obtained from lithiated ortho -methylbenzamides (Scheme 1b ), 4f while polycyclic isoindolines are accessible from ortho -lithiated benzyl chlorides (Scheme 1c ). 4h While contemplating the development of other annulation reactions using cyclic enolizable imines, our attention was drawn to the van Leusen imidazole synthesis (Scheme 1d ). 7 While this transformation is popular in medicinal chemistry and has been applied extensively to acyclic imines, 8 examples that use cyclic imines have remained limited.…”
Section: Table 1 Optimization Of the Annulation Reactio...mentioning
confidence: 99%